Persepsi Masyarakat Akademik Universiti Awam Tempatan Terhadap Sistem Perbankan Islam - Suzaida, Bakar (2004)
Three hundred questionnaires were distributed to lecturers of two public which is UUM and USM. All lecturers were selected randomly from various faculties. Questionnaires were developed to examine the level of understanding and in selecting a particular bank. Questionnaires can be divided into several parts which all questions relate to the understanding and knowledge towards Islamic banking, bank selection criteria, product usage and switching factors. Several questions in these questionnaires were adapted from previous study. One hundred fifty questionnaires were analyzed using mean and T-test to determine the most important factor in selecting criteria. The findings revealed that there are no significant different between two groups of lecturer. The findings also show that knowledge and understanding among lecturers still at moderate level. For selecting criteria, both group concern about fast and efficient services as a major factor. Besides that, this study also examines the usage of Islamic product or services as a major factor. Besides that, this study also examines the usage of Islamic product or services which the most frequent usage is ATM and it also can be relate to fast and efficient services. This study also examine the switching factors among respondent which the finding show the most important factors is low service quality and second is less experience among bank staff. Overall, customer interested with good service quality which this is a major factors in selecting bank criteria. The results also suggest that, Islamic bank should increase the level of service quality in order to obtain existing customers and built continuously relationship with Islamic bank.